PENGEMBANGAN MEDIA POP-UP BOOK 3D (PUBI) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK FASE C SEKOLAH DASAR - Nabhan Labib Musyaffa; Pupun Nuryani; Mubarok Somantri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research addresses the low critical thinking skills of students and the limited learning media available. This study aims to develop a 3D POP-UP BOOK (PUBI) medium to enhance the critical thinking skills of elementary school students in Phase C. The research method employed is Design and Development (D&D), utilizing the ADDIE development model (analysis, design, development, implementation, evaluation). Data collection techniques included questionnaires, observations, and pre-test and post-test administrations. The study used a Likert scale to measure the validation results from experts. The validation results indicate that the 3D POP-UP BOOK (PUBI) medium is highly suitable for use in learning, with an average percentage score of 93% (Very Suitable category) from material experts, 97% (Very Suitable category) from media experts, and 88% (Very Suitable category) from learning experts. Furthermore, there was an improvement in students' critical thinking skills, evidenced by the increased scores from the pre-test to the post-test. The overall average pre-test score was 50, which then increased to an average score of 83. Therefore, it can be concluded that the 3D POP-UP BOOK (PUBI) medium is highly suitable for use in classroom learning and is capable of improving students' critical thinking skills.